SUBMISSION SYSTEM DESIGNING FINANCING / CREDIT IN AL-JIBAAL BMT - Heni Mabruroh; Hariyanto, SKom, MM Hariyanto, SKom, MM (Jurnal Sistem Informasi, 2000)
Use of computer equipment in the field of administration in finance / credit helpssmooth running of the system that existed at the AL-JIBAAL BMT and can supportefficiency and productivity. In the old system in data processing still using manualsystems, which can lead to much accumulation of documents and files can be a timeof data loss or destruction of data. Circumstances of such data will impede thepresentation of data and require a long time in search of information.Use of Microsoft Access applications for finance administration / credit is helping toovercome the obstacles that occur in the preparation of reports, expedite informationfor AL-JIBAAL BMT or the parties who need and can avoid kerangkapan data.